A modified lignin / biochar coated slow-release fertilizer and its preparation method and application

The modified lignin/biochar coating addresses the limitations of existing slow-release fertilizers by offering a cost-effective, environmentally friendly, and biodegradable solution that enhances nutrient release and soil remediation.

CN115322045BActive Publication Date: 2024-12-17CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210859425.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-21
Publication Date
2024-12-17
Estimated Expiration
2042-07-21

AI Technical Summary

Technical Problem

Existing slow-release fertilizers face issues with non-renewable, expensive, and complex polymer coating materials that pollute the environment and reduce soil fertility, necessitating the development of a cost-effective and environmentally friendly coating solution.

Method used

A method involving acid precipitation pretreatment of lignin followed by esterification with an esterifying agent to modify lignin, combined with biochar, forms a coating for slow-release fertilizers, enhancing thermal stability and adsorption capabilities while being biodegradable.

Benefits of technology

The modified lignin/biochar coating provides sustained nutrient release, effective heavy metal adsorption, and improves soil quality, with a simple and economical preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115322045B_ABST
    Figure CN115322045B_ABST
Patent Text Reader

Abstract

The invention discloses a modified lignin / biochar coated slow-release fertilizer and a preparation method and application thereof. A lignin source is subjected to acid precipitation pretreatment to obtain acid precipitation lignin, and then the acid precipitation lignin is subjected to esterification reaction with an esterifying agent to obtain modified lignin, and then a fertilizer core is immersed in a mixed solution containing the modified lignin and biochar and dried to obtain the modified lignin / biochar coated slow-release fertilizer. The preparation method of the coated slow-release fertilizer provided by the invention is simple and easy, does not require expensive equipment, has a wide source of raw materials, is low in cost and is renewable, and the coated fertilizer also has the ability to remove heavy metals, can not only promote crop growth and development, but also can improve water bodies or soil, and improve soil water retention and air permeability, and has high added value and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation and application of slow-release fertilizers, and specifically relates to a modified lignin / biochar coated slow-release fertilizer and a preparation method and application thereof. Background Art

[0002] In the past few decades, in order to meet the growing demand for food worldwide, the use of fertilizers in agriculture has also increased dramatically. Moreover, due to the irrational application of fertilizers and the low actual utilization rate, soil pollution problems are serious, and the transfer of infiltrated soil water causes water pollution. At the same time, people's attention to the environment, health and sustainable use of natural resources is also increasing. Therefore, while ensuring food production, minimizing fertilizer losses, improving fertilizer utilization, and improving soil pollution are important tasks of current agricultural fertilizer scientific and technological innovation and an important guarantee for achieving sustainable agricultural development. In this case, slow-release / controlled-release fertilizers (S / CRFs) have received more and more attention. Compared with traditional fertilizers, S / CRFs have the advantages of high fertilizer utilization efficiency, sustainable nutrient supply, and low application cost. Therefore, the research and development of S / CRFs plays a very important role in promoting the development of green and sustainable agriculture. Among the current slow-release fertilizers, coated fertilizers are the most important type. Due to the current shortage and non-renewable nature of petroleum resources, the polymer film materials used in slow-release fertilizers are often not easy to degrade, accumulate in the soil, reduce soil fertility, and pollute the environment. In addition, the coating process of polymer materials is relatively complicated and the materials are expensive, which greatly increases the economic cost. Therefore, the most critical issue in the research of coated slow-release fertilizers is how to select coating materials that are widely available, low-priced, pollution-free, and can ensure that the fertilizer has good slow-release performance. Summary of the invention

[0003] Aiming at the defects of existing slow-release fertilizer coating materials that are non-renewable, complicated to prepare and expensive, the first object of the present invention is to provide a method for preparing a modified lignin / biochar coated slow-release fertilizer. The preparation method is easy to operate and low in cost.

[0004] The second object of the present invention is to provide a modified lignin / biochar coated slow-release fertilizer prepared by the above preparation method. The provided modified lignin / biochar coated slow-release fertilizer has good slow-release effect and can also improve soil.

[0005] The third object of the present invention is to provide an application of a modified lignin / biochar coated slow-release fertilizer prepared by the above preparation method. The modified lignin / biochar coated slow-release fertilizer is used for slow release of nutrients in still water or soil.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The invention discloses a method for preparing a modified lignin / biochar coated slow-release fertilizer. The method comprises the following steps: subjecting a lignin source to acid precipitation pretreatment to obtain acid precipitation lignin, then subjecting the acid precipitation lignin to an esterification reaction with an esterifying agent to obtain modified lignin, and then soaking and drying a fertilizer core in a mixed solution containing the modified lignin and biochar to obtain the modified lignin / biochar coated slow-release fertilizer. In the mixed solution containing the modified lignin and biochar, the mass fraction of the biochar is ≤5%, and in the mixed solution containing the modified lignin and biochar, the mass fraction of the modified lignin is 1-5%, preferably 2-4%.

[0008] The preparation method of the present invention first performs acid precipitation pretreatment on a lignin source, purifies the lignin raw material, and then performs esterification modification on it to obtain hydrophobic modified lignin, and then the modified lignin is compounded with biochar to form a coating. On the one hand, the addition of biochar can further enhance the thermal stability of the coating, prolong the thermal decomposition temperature and increase the number of surface functional groups of the coating, and at the same time can also adsorb heavy metals and improve the soil. The modified lignin / biochar coating material has excellent biodegradability.

[0009] Of course, the amount of biochar added needs to be effectively controlled. If too little is added, the hydrophobicity of the membrane will be too high. When the hydrophobicity is too high or too low, the fertilizer will not be released slowly or will be released too quickly. At the same time, if too little is added, the heavy metal adsorption performance will be reduced. If too much is added, its good hydrophilicity and excessive pore volume will increase the swelling performance of the membrane material, which is also not conducive to the slow release of the fertilizer.

[0010] In addition, the inventors unexpectedly discovered that after acid precipitation pretreatment and purification of sodium lignin sulfonate, the glass transition temperature can be greatly increased. After lipidation, the glass transition temperature is reduced but still remains above 50°C, which is beneficial to the processing, storage and transportation of slow-release fertilizers.

[0011] In a preferred embodiment, the lignin source is selected from at least one of sodium lignin sulfonate, enzymatic lignin, alkali lignin, kraft lignin, and lignin, preferably sodium lignin sulfonate.

[0012] The lignin sources used in the present invention are all of industrial grade or above.

[0013] In a preferred embodiment, the acid precipitation pretreatment process is as follows: dissolving sodium lignin sulfonate in water to obtain a solution, adding hydrochloric acid to the solution to adjust the pH to 1-4, settling for 12-24 hours, separating the solid from the liquid, washing and drying to obtain acid precipitation lignin (SL).

[0014] In the actual operation process, the solid-liquid separation is carried out by filtering, and the filter residue is washed with deionized water to neutrality and dried at 50°C to constant weight.

[0015] A preferred scheme is to use acid-precipitated lignin and an esterifying agent as raw materials and pyridine as a catalyst to carry out an esterification reaction to obtain modified lignin. The esterification reaction time is 1 to 3 hours, preferably 1 to 2 hours, and the reaction temperature is 10 to 50°C, preferably 20 to 40°C. The esterifying agent is selected from one of acetyl chloride, octanoyl chloride, dodecanoyl chloride, and hexadecanoyl chloride. The solid-liquid mass volume ratio of the acid-precipitated lignin to the esterifying agent is 0.2 to 1 g: 2 to 7 mL, and the volume ratio of the esterifying agent to pyridine is 0.5 to 2: 0.8, preferably 1: 0.8.

[0016] More preferably, the esterification agent is hexadecanoyl chloride.

[0017] The inventors found that lignin modified with hexadecanoyl chloride has the highest hydrophobicity, and more hydrophilic biochar can be introduced to adjust the hydrophobic and hydrophilic properties, thereby optimizing the comprehensive performance of the modified lignin / biochar coated slow-release fertilizer.

[0018] Further preferably, the acid-precipitated lignin is dissolved in NN dimethylformamide and ultrasonically treated for 2 to 7 minutes, and then pyridine and an esterifying agent are added to carry out an esterification reaction. After the esterification reaction is completed, the resulting reaction liquid is poured into 300 to 700 mL of hydrochloric acid with a mass fraction of 1 to 3% to terminate the reaction, filtered, precipitated, ground and washed with distilled water and ethanol, and then freeze-dried to obtain the modified lignin, and the solid-liquid mass volume ratio of the acid-precipitated lignin to NN dimethylformamide is 0.2 to 1 g: 10 to 30 mL.

[0019] In a preferred embodiment, the biochar is obtained by removing lignin from poplar sawdust to obtain delignified sawdust, which is then pyrolyzed under a protective atmosphere, and the obtained pyrolysis products are then subjected to alkali activation treatment.

[0020] The inventors unexpectedly discovered that using poplar sawdust as the raw material for biochar and preparing the resulting biochar in the manner of the present invention has very excellent adsorption properties for hexavalent chromium, so that the modified lignin / biochar coated slow-release fertilizer of the present invention not only has excellent slow-release properties, but also can adsorb hexavalent chromium, and can be used in chromium-contaminated soil, and at the same time as a fertilizer and soil remediation agent.

[0021] Further preferably, the process of lignin removal treatment is: placing poplar sawdust in an alkaline solution containing NaOH and Na2SO3, reacting at 90-110°C for 1-10 hours to obtain alkali-boiled poplar sawdust, then soaking the alkali-boiled poplar sawdust in H2O2 solution for 1-3 hours, adding ammonia water during soaking to adjust the pH to 9-11, and finally washing the sawdust with deionized water until the solution is neutral, and drying to obtain delignified sawdust.

[0022] Further preferably, the alkali solution containing NaOH and Na2SO3 has a concentration of 0.1 to 2 mmol L –1, preferably 1 to 1.5 mmol L –1 The NaOH solution with a concentration of 0.1-2 mmol L –1 , preferably 0.1 to 0.5 mmol L –1 The volume ratio of the NaOH solution to the Na2SO3 solution is 0.5 to 2:1, preferably 1:1.

[0023] More preferably, in the H2O2 solution, the mass fraction of H2O2 is 2-5%.

[0024] Further preferably, the pyrolysis temperature is 650-750°C, the pyrolysis time is 1-3h, and the heating rate is 2-10°C min –1 .

[0025] More preferably, the protective atmosphere is N2.

[0026] Further preferably, the alkali activation treatment process is to mix the pyrolysis product with KOH, the mass ratio of KOH to the pyrolysis product is 3 to 5:1, and then perform heat treatment under a protective atmosphere, the heat treatment temperature is 650 to 750°C, the heat treatment time is 1 to 3 hours, and the heating rate is 2 to 10°C min –1 .

[0027] In actual operation, the pyrolysis product is mixed with KOH, water is added and stirred to dissolve the KOH, and then heat-treated after drying. After the heat treatment is completed, it is thoroughly washed several times with HCl to remove soluble inorganic salts, and then washed with distilled water until the pH reaches neutral, and dried to obtain biochar, preferably in a vacuum oven at 100°C for 12 hours.

[0028] In a preferred embodiment, the method for obtaining the mixed solution containing modified lignin and biochar is as follows: dissolving a binder in dichloromethane to obtain a solution containing the binder, dissolving modified lignin in 1,4-dioxane to obtain a solution containing modified lignin, mixing the solution containing the binder with the solution containing the modified lignin to obtain a mixed solution, adding biochar to the mixed solution to obtain a mixed solution containing modified lignin and biochar, wherein the binder is polyvinyl alcohol (PLA).

[0029] During the experimental exploration, the obtained mixed solution containing modified lignin and biochar was poured on a culture dish and dried at room temperature to obtain a coating material (PPAC film).

[0030] Further preferably, in the solution containing the binder, the mass fraction of polyvinyl alcohol is 20% to 40%, in the solution containing the modified lignin, the mass fraction of the modified lignin is 3% to 7%, and the volume ratio of the solution containing the binder to the solution containing the modified lignin is 0.5 to 2:1, preferably 1:1.

[0031] Further preferably, in the mixed solution containing modified lignin and biochar, the mass fraction of biochar is 1 to 5%, preferably 2 to 4%.

[0032] In a preferred embodiment, the fertilizer core is urea, and the particle size of the urea is 4 to 5 mm.

[0033] In a preferred embodiment, the soaking time is 20 to 40 seconds, preferably 30 seconds.

[0034] In the actual operation process, after soaking, the materials are carefully separated and placed on a sieve, and then quickly dried with a hair dryer to obtain a modified lignin / biochar coated slow-release fertilizer.

[0035] In a preferred embodiment, in the modified lignin / biochar coated slow-release fertilizer, the coating layer has a thickness of 100 to 150 μm.

[0036] In the present invention, the thickness of the coating layer is controlled within the above range, and the final comprehensive performance is optimal.

[0037] In the modified lignin / biochar coated slow-release fertilizer of the present invention, the nitrogen content on the surface of the coating layer is high and the surface of the coating layer is tight.

[0038] The present invention also provides a modified lignin / biochar coated slow-release fertilizer (PPAC-CSRF) prepared by the above preparation method.

[0039] The present invention also provides an application of a modified lignin / biochar coated slow-release fertilizer prepared by the above preparation method, wherein the modified lignin / biochar coated slow-release fertilizer is used for nutrient slow-release in still water or soil.

[0040] In a preferred embodiment, the modified lignin / biochar coated slow-release fertilizer is used for slow-release of nutrients in still water or soil contaminated with hexavalent chromium.

[0041] The present invention explores the sustained release of PPAC-CSRF in water through a static water experiment. Specifically: 0.5 g of urea and PPAC-CSRF were taken and placed in a 200 mL glass bottle filled with 100 mL of deionized water. 2 mL of liquid sample was regularly extracted from the glass bottle and the urea concentration was determined by the para-diaminobenzaldehyde method (PDAB) colorimetric method at a wavelength of 420 nm. In addition, 2 mL of distilled water was added to the bottle to keep the volume constant, and each sample was repeated three times.

[0042] Furthermore, the urea and PPAC-CSRF weighed in the present invention are 0-1 g, and the deionized water is 100 mL. 1-3 mL of liquid sample is regularly extracted from the glass bottle to determine the urea concentration using the p-diaminobenzaldehyde method (PDAB) colorimetric method, preferably 2 mL.

[0043] The present invention explores the slow release of PPAC-CSRF in soil through a soil column leaching experiment. The operation is as follows: a PVC pipe is used as a soil pile. The bottom of the PVC pipe is sealed with a double-layer iron mesh. First, quartz sand is filled into the bottom of the PVC column, and then 200g of air-dried soil is mixed with the quartz sand, and the top layer is covered with quartz sand. Before measuring the release of PPAC-CSRF, deionized water is immersed in the soil column so that the water just soaks the soil column but does not flow out. Then, deionized water is added at each interval leaching, the soil exudate is collected and filtered, and then the release amount of urea is determined by the para-diaminobenzaldehyde method (PDAB) colorimetric method.

[0044] Furthermore, the present invention adopts a PVC pipe with a diameter of 4.00 cm and a length of 20.00 cm. The double-layer iron mesh is selected to be 80-120 mesh, preferably 100 mesh, for the experiment.

[0045] Furthermore, the quartz sand at the bottom and top is 40-60g, preferably 50g. The ratio of the soil to the quartz sand in the middle is 0.3g / 100g.

[0046] Furthermore, the leaching time was 1, 3, 5, 10, 15, 20, 25, 30, 35, and 40 days at each interval, and the soil exudate was collected and filtered, and then the urea release was determined by the p-diaminobenzaldehyde (PDAB) colorimetric method.

[0047] The present invention conducts a batch adsorption experiment of Cr(VI). Specifically, batch adsorption measurements of Cr(VI) of different concentrations are carried out in a conical flask. Hexavalent chromium of different concentrations is calibrated using potassium dichromate. A Cr(VI) solution of a certain concentration is taken, a certain amount of adsorbent is added, and the pH value of the solution is adjusted with HCl and NaOH. After adsorption, the solution is filtered with a 0.45 μm filter membrane, and the Cr(VI) concentration is determined with an ultraviolet spectrophotometer.

[0048] Furthermore, the present invention uses 50mL of chromium ion concentration of 0 to 20mg L –1 The adsorption experiment was carried out using the solution as an example, and the addition amount of PPAC-CSRF was between 0.005 and 0.4 g.

[0049] Furthermore, the pH during adsorption is 4 to 6, preferably pH 5; the temperature range is 20° C. to 50° C., preferably 25° C., and the adsorption time is at least 48 hours.

[0050] Furthermore, the pH value of the heavy metal solution was adjusted with HCl and NaOH; after adsorption, it was filtered with a 0.45 μm filter membrane.

[0051] The beneficial effects of the present invention are:

[0052] The preparation method of the present invention first performs acid precipitation pretreatment on the lignin raw material, purifies the lignin raw material, and then performs esterification modification on it to obtain hydrophobic modified lignin, and then the modified lignin is compounded with biochar to form a coating. On the one hand, the addition of biochar can further enhance the thermal stability of the coating, prolong the thermal decomposition temperature and increase the number of surface functional groups of the coating, and at the same time can also adsorb heavy metals and improve the soil. The modified lignin / biochar coating material has excellent biodegradability.

[0053] The present invention makes the biomass materials lignin and poplar sawdust widely available, economical and environmentally friendly. The hydrophobicity of lignin is increased by modification, thereby enhancing the function of the lignin as a membrane material. The biochar prepared by using poplar sawdust has a certain heavy metal adsorption capacity, especially for Cr(VI), and has very excellent repair performance. The batch Cr(VI) adsorption experiment can lay a certain foundation for practical application.

[0054] The intermediate product and the final finished product of the present invention have the following characteristics:

[0055] 1. After lignin is modified by esterification, the hydroxyl group of lignin is significantly reduced, and a new absorption band of C=O extending from the ester bond appears. In addition, since the acyl chloride contains a large amount of -CH2 and -CH3, the 2940 cm -1 、2840cm -1 The CH stretching vibration absorption peak is significantly enhanced.

[0056] 2. After modification, the hydrophilicity of lignin decreased and the hydrophobicity increased. The hydrophobic contact angle of lignin modified with hexadecanoyl chloride still reached 116.54° after stabilization for 3 minutes. TMA characterization showed that the glass transition temperature of the modified lignin product increased with the extension of the acyl chloride chain: ACSL (Tg = 57.5°C) < CCSL (Tg = 58.16°C) < LCSL (Tg = 81.97°C) < PCSL (Tg = 110.42°C).

[0057] 3. After chemical pretreatment, the poplar sawdust showed a layered structure, the color became lighter, and the amount of lignin decreased from 28.75% to 6.39%. After KOH activation, the prepared ACDW had a carbon content of 970.5 m 2 g -1 The specific surface area is increased, and the volume of micropores and mesopores is further increased.

[0058] 4. The prepared PPAC membrane has a certain hydrophobicity, and as the content of biochar increases, the contact angle of the PPAC membrane continues to decrease. When the biochar content is 0%, the contact angle of the PPAC membrane is 109.92°. After adding biochar, due to the hydrophilic nature of biochar, when the biochar content is 4%, the contact angle drops to 83.58°.

[0059] 5. SEM shows that the surface of the PPAC membrane is a uniform porous structure. When the biochar content is 0%, there is a small amount of pore structure on the surface of the PPAC membrane, and the surface is smooth. After adding biochar, the porous structure on the membrane surface is evenly distributed and the pore size increases. When the biochar content is higher, its good hydrophilicity and excessive pore volume will lead to an increase in the swelling performance of the membrane material, which is not conducive to the slow release of fertilizers. Among them, the comprehensive performance of the PPAC with a biochar content of 3% is the best.

[0060] 6. FTIR, thermogravimetric analysis and biodegradability of PPAC membranes containing 3% biochar were performed, indicating that the addition of biochar can enhance the thermal stability of PPAC membranes, prolong the thermal decomposition temperature and increase the number of surface functional groups of PPAC membranes. The prepared coating material has good biodegradability.

[0061] 7. The SEM microscopic morphology of the prepared coated fertilizer PPAC-CSRF shows that the surface of the slow-release fertilizer is dense, smooth and uniform, the thickness of the coating layer is about 100-150 μm, and the coating layer accounts for about 15.706% of the total weight of the fertilizer. The surface of the coating layer contains only 5.67% nitrogen, which shows that the surface of the coating layer is tight.

[0062] 8. Cr(VI) adsorption experiments show that PPAC-CSRF has good adsorption performance, with a maximum adsorption capacity of 40.39 mg g –1 , which is of great significance to soil environment and water bodies in practical applications.

[0063] 9. PPAC-CSRF has good slow-release performance. The release period of pure urea in static water is 25 minutes, while the release period of PPAC-CSRF is 25 hours, which is 72 times the release period of uncoated urea. The soil column leaching experiment shows that the cumulative release of urea in PPAC-CSRF within 20 hours is 38.35%, while pure urea has been completely released in 20 days.

[0064] 10. The release process of PPAC-CSRF was fitted using sustained release kinetics, and it was found that the sustained release process of PPAC-CSRF in soil involves two sustained release mechanisms: diffusion and dissolution.

[0065] In summary, the preparation method provided by the present invention is simple and easy, does not require expensive equipment, has a wide range of raw materials, is low-cost and renewable, and the modified lignin / biochar coating material has excellent biodegradability and heavy metal adsorption performance, and can also be expanded to other biomass materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0066] Figure 1 The infrared spectra of the lignin in Example 1 and the lignin modified with four kinds of acyl chlorides are shown in FIG.

[0067] Figure 2 ] are the contact angles of lignin in Example 1 and lignin modified with four acid chlorides.

[0068] Figure 3 Thermomechanical analysis curves of SL, ACSL, CCSL, LCSL and PCSL prepared in Example 1 are shown in FIG. Figure 3 (a) is SL, Figure 3 (b) is ACSL, Figure 3 (c) CCSL, Figure 3 (d) LCSL and Figure 3 (e) is the thermomechanical analysis curve of PCSL.

[0069] Figure 4 This is an analysis diagram of three components of poplar sawdust after delignification in Example 1.

[0070] Figure 5 The contact angles of the PPAC films with five different biochar contents prepared in Example 1.

[0071] Figure 6 These are SEM images of the morphology of the PPAC membranes with five different biochar contents prepared in Example 1. Figure 6 (a) 0%-PPAC, Figure 6 (b) 1%-PPAC, Figure 6 (c) 2%-PPAC, Figure 6 (d) 3%-PPAC, (e) 4%-PPAC (the insets are the corresponding enlarged images).

[0072] Figure 7 Biodegradability of the PPAC membrane with 3% biochar content and the prepared PPAC-CSRF in Example 1.

[0073] Figure 8 is the thermogravimetric analysis diagram of the PPAC membrane in Example 1, wherein Figure 8 (a) Thermogravimetric analysis of PPAC membrane with 0% biochar content. Figure 8 (b) Thermogravimetric analysis of PPAC membrane with 3% biochar.

[0074] Fig. 9 This is an electron microscope image of the morphology of the PPAC-CSRF fertilizer prepared in Example 1. Fig. 9 (a) Surface SEM of PPAC-CSRF. Fig. 9 (b) Cross-sectional SEM of PPAC-CSRF, Fig. 9 (ce)Surface element distribution of PPAC-CSRF, Fig. 9 (f) Surface element content of PPAC-CSRF.

[0075] Fig.10 This is a graph showing the Cr(VI) adsorption capacity of the PPAC-CSRF fertilizer prepared in Example 1.

[0076] Fig.11 This is the sustained release curve of PPAC-CSRF in water in Example 1.

[0077] Fig.12 This is the sustained release curve of PPAC-CSRF in soil in Example 1.

[0078] Fig.13 This is the application of PPAC-CSRF in the rice seedling experiment in Example 1. DETAILED DESCRIPTION

[0079] The following examples are intended to further illustrate the present invention, but are not intended to limit the present invention.

[0080] Embodiment 1:

[0081] (1) Modification of lignin:

[0082] First, according to the principle of alkali dissolution and acid precipitation of sodium lignin sulfonate, a certain mass of industrial-grade sodium lignin sulfonate was dissolved in deionized water (m / v=1:20), and then hydrochloric acid was added to adjust the pH of the solution to 3. The solution was allowed to settle for 12 hours and filtered. The filter residue was washed with deionized water until neutral and dried at 50°C to constant weight, which was recorded as acid-precipitated lignin (SL).

[0083] SL and acyl chloride were used as raw materials and pyridine was used as catalyst for esterification reaction. 0.5 g of SL was dissolved in 20 mL of NN dimethylformamide (DMF) solution, ultrasonicated for 5 min, 5 mL of pyridine solution and 4 mL of acyl chloride (AC-C2, OC-C8, LC-C 12 ) and reacted at room temperature for 2 h. Then, under the same experimental conditions, hexadecanoyl chloride (PC-C 16After the reaction was completed, the solution was poured into 500 mL of 2% hydrochloric acid to terminate the reaction, the precipitate was filtered, ground and washed with excess distilled water and ethanol, and then freeze-dried. The modified products were recorded as ACSL, OCSL, LCSL and PCSL, respectively.

[0084] (2) Preparation of biochar:

[0085] Poplar sawdust (PW) was soaked in a 1:1 mixed aqueous solution of 1.25M NaOH and 0.2M Na2SO3. It was steamed at 100℃ for 5 hours and then washed. Then 3% H2O2 solution was added with ammonia water to adjust the pH to 10 and treated at 80℃ for 2 hours to remove residual lignin. Finally, it was vacuum freeze-dried and recorded as DW. A certain mass of DW sample was weighed and placed in a tubular atmosphere furnace for heat treatment. The specific operation is: set the heating program as: first at 5℃ min -1 The heating rate was increased to 700℃ and kept for 2h, named CDW. Then KOH was used to grind CDW uniformly at a mass ratio of 1:4. Subsequently, ACDW was prepared under the same pyrolysis conditions.

[0086] (3) Preparation of modified lignin / biochar composite membrane:

[0087] PLA was dissolved in dichloromethane at a concentration of 30% (w / v), and PCSL was dissolved in 1,4-dioxane at a concentration of 6% (w / v). 30% PLA and 6% PCSL solution were mixed in a volume ratio of 1:1, and then different masses of biochar were added to the mixture to prepare a PPAC mixture of PLA-PCSL-layered porous biochar (ACDW), in which the mass fractions of biochar in the PPAC mixture were 0%, 1%, 2%, 3%, 4%, and 5%, respectively. The mixture was poured on a culture dish and dried at room temperature for 2 hours to directly obtain a membrane, which is called a PPAC membrane.

[0088] (4) Preparation of modified lignin / biochar coated urea:

[0089] The coated urea slow-release fertilizer was prepared by a simple dip-coating method. Operation method: Select urea particles with a diameter of 4 to 5 mm, soak them in the PPAC mixture prepared in the third step for 30 seconds, carefully separate them, place them on a sieve, and quickly dry them with a hair dryer to obtain PPAC coated slow release fertilizer (CSRF), which is recorded as PPAC-CSRF.

[0090] Testing methods and results

[0091] 1. Using the acid-precipitated lignin prepared in the first step and the four modified lignins as raw materials, Fourier transform infrared spectroscopy analysis was performed to determine whether the reaction proceeded smoothly.

[0092] Figure 1 The infrared spectra of lignin modified by four acyl chlorides in Example 1 show that a large number of hydroxyl groups in lignin provide reaction sites for the esterification modification of lignin. Figure 1 As shown in Figure 2, the hydroxyl groups in lignin were esterified by acetyl chloride, octanoyl chloride, dodecanoyl chloride or hexadecanoyl chloride, respectively, to form lignin-based hydrophobic polymers with fatty chains. The FTIR spectrum shows that the free OH in the modified lignin generated by esterification is at 3424 cm -1 The stretching vibration absorption peak at 1740-1760cm -1 A new absorption band extending from the ester bond of C=O was detected at 2800-3000cm -1 The stretching of aliphatic CH in the region also increases with the increase of aliphatic chain length. In addition, since the acyl chloride contains a large amount of -CH2 and -CH3, the 2940 cm -1 、2840cm -1 The CH stretching vibration absorption peak of lignin was significantly enhanced. The reaction with acyl chloride consumed a large number of phenolic hydroxyl groups and alcoholic hydroxyl groups in lignin, so the absorption peak at 1330 cm -1 The absorption peak at is significantly weakened.

[0093] 2. Using the acid-precipitated lignin prepared in the first step and four modified lignins as raw materials, water contact angle analysis was performed to determine the hydrophobicity of the modified lignin.

[0094] Figure 2 The contact angles of lignin after modification with four acyl chlorides in Example 1. The successful reaction of the acyl chloride carbon chain will increase the hydrophobicity of lignin and reduce the brittleness of lignin. Figure 2The results show that lignin is brown, and after esterification, ACSL and CCSL are black. This is because the two modified products are easy to agglomerate at room temperature and the color turns black. After the extension of the acyl chloride carbon chain, LCSL and PCSL show a trend of gradually turning yellow and appearing in powder form. Moreover, the hydrophobicity of esterified lignin gradually increases after the extension of the acyl chloride carbon chain. The hydrophobic contact angle of lignin is 43.94° within 3s and becomes 10.56° after 3min, indicating that the hydrophilicity of acid-precipitated lignin is very high. As a coating material, the higher hydrophilicity cannot guarantee the slow release of fertilizer. After esterification modification, the hydrophobicity gradually increases. The hydrophobic contact angle from ACSL to PCSL gradually increases from 80.95° to 116.56°, and PCSL still has a hydrophobic contact angle of 116.54° after 3min, which has strong hydrophobic stability. The hydrophobic property of modified lignin can ensure the slow-release effect of the slow-release material, has good water barrier properties, and can improve the utilization rate of fertilizers.

[0095] 3. Using the acid-precipitated lignin prepared in the first step and four modified lignins as raw materials, thermomechanical analysis was carried out to determine the glass transition temperature of lignin after modification by the modifier.

[0096] Figure 3 Thermomechanical analysis curves of (a) SL, (b) ACSL, (c) CCSL, (d) LCSL and (e) PCSL in Example 1. We used thermomechanical analysis (TMA) to determine the glass transition temperature (Tg) of the original and modified lignin samples. The mechanism is to heat the sample at a certain heating rate, so that the sample deforms with the increase of temperature under a constant small load, and measure the temperature-deformation curve of the sample. The results are shown in Figure 3 As shown in the figure, TG increases with the extension of the acyl chloride chain: ACSL (Tg = 57.5 ° C) < CCSL (Tg = 58.16 ° C) < LCSL (Tg = 81.97 ° C) < PCSL (Tg = 110.42 ° C). After modification, the molecular weight of the modified product will increase, so the glass transition temperature of the modified lignin product will become higher and higher; compared with the unmodified lignin (Tg = 146.44 ° C), the glass transition temperature of the modified lignin is significantly reduced. This is because the free volume of the polymer increases after modification, and the hydrogen bonds inside the lignin polymer are destroyed, resulting in an increase in the fluidity of the modified lignin molecules, thereby reducing the glass transition temperature. However, it can be seen that although the glass transition temperature has decreased, it is still maintained above 50 ° C, which is conducive to the processing, storage and transportation of the final slow-release fertilizer.

[0097] 4. The delignified poplar wood and poplar wood prepared in the second step were subjected to the National Renewable Energy Laboratory (NREL) standard measurement to measure the composition changes of cellulose, lignin and hemicellulose.

[0098] Figure 4 The following are the three components of poplar wood chips after delignification. The contents of cellulose, hemicellulose and lignin in poplar wood before and after chemical pretreatment were measured using the National Renewable Energy Laboratory (NREL) standard. All test values ​​and normalized values ​​of cellulose, hemicellulose and lignin are summarized in Figure 4 , the results showed that after delignification, cellulose decreased from 42.36% to 33.43%, hemicellulose decreased from 14.56% to 7.65%, and lignin decreased from 28.75% to 6.39%.

[0099] 5. The water contact angle of the five PPAC membranes prepared in the third step was used to analyze the changes in hydrophobicity after the addition of biochar.

[0100] Figure 5 The contact angles of the prepared PPAC membranes with five different biochar contents were tested to study the changes in the hydrophobicity of the PPAC membranes after adding biochar. Figure 5 As shown in the figure, when there are only modified lignin and polylactic acid, the contact angle of the PPAC film is 109.92°. This is because the added PCSL is hydrophobic, and polylactic acid itself has a certain water barrier, resulting in the composite film showing a strong hydrophobicity. As the content of biochar continues to increase, the contact angle of the PPAC film gradually decreases, indicating that the addition of biochar increases the hydrophilicity of the composite film. When 4% biochar is added, the contact angle is 83.58°. The hydrophobic coating material can ensure the slow release effect of the slow release material. When the hydrophobicity is too high or too low, it will cause the fertilizer to not be slow released or to be slow released too quickly, so it is necessary to choose a PPAC membrane material with a suitable hydrophobic contact angle.

[0101] 6. The morphology of the five PPAC membranes prepared in the third step was analyzed using scanning electron microscopy.

[0102] Figure 6 These are SEM images of the morphology of the PPAC membranes with five different biochar contents prepared in Example 1. Figure 6 (a) 0%-PPAC, Figure 6 (b) 1%-PPAC, Figure 6 (c) 2%-PPAC, Figure 6 (d) 3%-PPAC, Figure 6(e) 4%-PPAC (the inset is the corresponding enlarged image). We further characterized the microstructure of the PPAC membrane by SEM ( Figure 6 ).like Figure 6 As shown in the figure, before adding biochar, the PPAC membrane has a dense structure and a smooth surface. After adding biochar, it can be seen that a small amount of evenly distributed pore structure begins to appear on the membrane surface, and the surface becomes rough. As the amount of biochar continues to increase, the density of the porous structure increases and the pore size increases with the increase in biochar content. The porous structure of the coating material is a key factor affecting the rate of water penetration into the fertilizer. The increase in pore size will accelerate the release of nutrients, but the increase in the amount of biochar can increase the adsorption of heavy metals. Combined with the contact angle and morphology analysis, the performance of the PPAC membrane with a 3% biochar content is optimal.

[0103] 7. To study the degradability of PPAC membranes, five PPAC membranes prepared in step 3 were buried 10 cm below the soil. These samples were periodically removed from the soil, washed, dried with filter paper, and weighed to determine their weight loss.

[0104] Figure 7 The biodegradability of the PPAC film with 3% biochar content and the prepared PPAC-CSRF in Example 1. In order to study the biodegradability of the prepared coating material, we conducted soil burial experiments on the prepared PPAC with 0% biochar and 3% biochar content, as well as the coating layer after the slow release. The results are shown in Figure 7 As shown in the figure, the results show that the PPAC membrane without biochar degraded by 54.38% after 90 days, cracks appeared on the membrane surface, and the edges fell off, showing good degradability. The loss of its mass is mainly due to polylactic acid, because the degradation cycle of polylactic acid is within 90 to 180 days. The degradation of the PPAC membrane with biochar slowed down. After 90 days, it only degraded by 28.59%. This may be because biochar itself has strong stability. It can not only aggregate other substances in the soil, but also play a role in connecting PLA and PCSL in the PPAC membrane, making the connection between the three closer, thereby slowing down the biodegradability. Therefore, PPAC with biochar showed difficult degradation. The slow-released coating layer degraded faster after 90 days, probably because the slow release of fertilizer increased the pore size on the surface of the coating layer, and the microorganisms and enzymes in the soil were more likely to adhere to it, thereby reacting with the coating layer and making it easier to degrade. This degradation method is more conducive to plant growth.

[0105] 8. In order to study the thermal analysis performance of PPAC membrane, the thermal decomposition properties of the PPAC membrane with 0% biochar content and the PPAC membrane with 3% biochar content prepared in the third step were analyzed using a thermogravimetric analyzer.

[0106] Figure 8is the thermogravimetric analysis diagram of the PPAC membrane in Example 1, wherein Figure 8 (a) Thermogravimetric analysis of PPAC membrane with 0% biochar content. Figure 8 (b) Thermogravimetric analysis of PPAC membrane with 3% biochar. Figure 8 (b) It can be seen that the PPAC membrane containing biochar has better thermal stability, a higher initial decomposition temperature, and significant mass loss occurs at 300°C. The initial decomposition temperature of the PPAC membrane without biochar is 140°C.

[0107] 9. In order to explore the surface changes of the PPAC-CSRF prepared in the fourth step, we used scanning electron microscopy to analyze the surface changes and surface element analysis of the fertilizer after coating.

[0108] Fig. 9 This is an electron microscope image of the morphology of the PPAC-CSRF fertilizer prepared in Example 1. Fig. 9 (a) Surface SEM of PPAC-CSRF. Fig. 9 (b) Cross-sectional SEM of PPAC-CSRF, Fig. 9 (ce)Surface element distribution of PPAC-CSRF, Fig. 9 (f) Surface element content of PPAC-CSRF. Fig. 9 As shown in the figure, the surface (film layer) of the slow-release fertilizer is relatively dense, smooth and uniform, indicating that the material has good film-forming properties. The SEM image of the fertilizer cross section shows ( Fig. 9 (b)), the coating layer is tightly wrapped on the surface of urea, and its thickness is about 100-150μm. The overall mass of the fertilizer before and after coating was calculated by the formula, and it was found that the coating layer accounted for about 15.71% of the total mass of the fertilizer, indicating that the coating material did not significantly increase the mass of the slow-release fertilizer, reflecting its lightweight characteristics. Through EDS elemental analysis of the surface of the slow-release fertilizer, it was found that the surface of the coating layer contained almost no nitrogen (the mass ratio was only 5.67%), indicating that the surface of the coating layer was tight and there was no fertilizer leakage.

[0109] 10. To explore the ability of the prepared PPAC-CSRF to adsorb heavy metals, hexavalent chromium Cr(VI) was used as a model pollutant and chromium adsorption was performed. Specifically, 5, 10, and 15 mg L -1 50 mL of Cr(VI) solution was added with two sustained-release PPAC-CSRF as adsorbents (masses were 0.03 g, 0.018 g, and 0.024 g, respectively). The pH of the solution was adjusted to 5, and the solution was continuously shaken at 150 rpm for 2880 min on a thermostatic shaker. The absorbance was measured by a UV spectrophotometer, and the concentration difference before and after adsorption was calculated. The adsorption capacity was calculated.

[0110] Fig.10 Figure 2 is a graph showing the Cr(VI) adsorption capacity of the PPAC-CSRF fertilizer prepared in Example 1. Generally speaking, the concentration of Cr(VI) in chromium-contaminated soil or water environments does not exceed 10 mg L –1 Therefore, this experiment used concentrations of 5, 10, and 15 mg L –1 The adsorption experiment of Cr(VI)-containing solution was carried out to evaluate the ability of PPAC-CSRF to adsorb Cr(VI) under different concentration conditions. Fig.10 As shown in the figure, when the concentration of Cr(VI) solution is 5 mg L –1 When , the adsorption amount of PPAC-CSRF was 31.13 mg g –1 When the concentration of Cr(VI) solution is 10 mg L –1 When –1 When the concentration is 15 mg L –1 When , the adsorption capacity did not increase significantly, which was 40.39 mg g –1 PPAC-CSRF adsorbent has a –1 Under the concentration conditions, the adsorption saturation point is basically reached and no more chromium ions can be absorbed and stored.

[0111] 11. The soil column leaching method was used to investigate the slow release of the PPAC-CSRF fertilizer prepared in the fourth step. A PVC pipe with a diameter of 4.00 cm and a length of 20.00 cm was used as a soil pile. The bottom of the PVC pipe was sealed with a double-layer iron mesh. First, quartz sand was filled into the bottom of the PVC column, and then 200 g of air-dried soil was mixed with quartz sand at a ratio of 0.3 g / 100 g of quartz sand to soil. The top layer was covered with 50 g of quartz sand. First, deionized water was immersed in the soil column so that the water just soaked the soil column but did not flow out. Then, 30 mL of deionized water was added at each interval leaching (1, 3, 5, 10, 15, 20, 25, 30, 35, 40 d), the soil exudate was collected and filtered, and then the release of urea was determined by the para-diaminobenzaldehyde method (PDAB) colorimetric method.

[0112] Fig.11 The slow-release curve of PPAC-CSRF in water in Example 1. This study used a static water dissolution experiment to explore the nitrogen release law of PPAC-CSRF slow-release nitrogen fertilizer in water. The results are shown in Fig.11As shown in the figure, from the nitrogen release curve of pure urea, it can be seen that when urea is in static water, it will dissolve quickly. After about 5 minutes, the urea will be completely dissolved in the water. The release period of urea is 25 minutes, and the cumulative amount released is 90.69%. The release of PPAC-CSRF is a slow process. At 5 hours, only 23.2% is released. At 25 hours, the urea is completely released, reaching 88.91%, which is 72 times that of the uncoated one. The static water dissolution experiment shows that PPAC-CSRF has good sustained release performance.

[0113] 12. This experiment uses rice to study the seedling growth of the PPAC-CSRF fertilizer prepared in the fourth step. This paper explores the potential application of this slow-release fertilizer as a plant nitrogen fertilizer through a rice seed germination experiment. Using rice seeds as materials, the effect of this fertilizer on seedling growth was studied. The experiment was carried out under three different conditions: blank, urea and PPAC-CSRF. The samples were placed in an incubator at 30°C. Seeds with a bud length of about 5 cm were selected, and seedling growth was studied under the same temperature, moisture and sunlight conditions. The growth of total biomass of each group was measured.

[0114] Fig.12 is the slow release curve of PPAC-CSRF in soil in Example 1. We used soil column leaching experiments to explore the nitrogen release law of urea and PPAC-CSRF in soil. The results are as follows Fig.12 As shown in the figure, from the leaching curve of pure urea, it can be seen that when urea is applied to the soil as nitrogen fertilizer, the nutrients in the urea will be rapidly decomposed under the action of soil microorganisms, water and various enzymes. The urea release in 1, 5, 15 and 20 days is 3.31%, 35.8%, 81.59% and 89.54%, and most of the nutrients in urea are released within 15 days after application to the soil. The cumulative release of urea in PPAC-CSRF in 1, 5, 15 and 20 days is 1.18%, 4.47%, 20.46% and 38.35%, respectively. Compared with the release rate of pure urea, it is reduced by 2.13%, 31.33%, 61.13% and 51.19%, respectively. It shows that the coated urea has good slow release performance.

[0115] 13. This experiment uses rice to study the seedling growth of the PPAC-CSRF fertilizer prepared in the fourth step. This paper explores the potential application of this slow-release fertilizer as a plant nitrogen fertilizer through a rice seed germination experiment. Using rice seeds as materials, the effect of this fertilizer on seedling growth was studied. The experiment was carried out under three different conditions: blank, urea and PPAC-CSRF. The samples were placed in an incubator at 30°C. Seeds with a bud length of about 5 cm were selected, and seedling growth was studied under the same temperature, moisture and sunlight conditions. The growth of total biomass of each group was measured.

[0116] Fig.13 This is the application of PPAC-CSRF in the rice seedling experiment in Example 1. Fig.13 It can be seen that among the blank group experiments, urea group and PPAC-CSRF group, the rice seedlings cultured in conical flasks and test tubes were the highest in the PPAC-CSRF group.

[0117] Comparative Example 1

[0118] The other conditions were the same as those in Example 1, except that the acid-precipitated lignin (SL) was directly dissolved in 1,4-dioxane at a concentration of 6% (w / v). Then 3% biochar was added to the mixture to obtain a coated slow-release fertilizer. The obtained slow-release fertilizer, due to its strong hydrophilicity, completely released nutrients in a short period of time, and did not meet the requirements of slow-release fertilizer.

[0119] Comparative Example 2

[0120] The other conditions were the same as those in Example 1, except that industrial sodium lignin sulfonate was directly subjected to hexadecanoyl chloride (PC-C 16 ) esterification reaction. Due to the large amount of impurities, the yield of successfully modified PCSL is low, less than 20% after acid precipitation.

Claims

1. A method for preparing a modified lignin / biochar coated slow-release fertilizer, characterized in that: The lignin source is subjected to acid precipitation pretreatment to obtain acid precipitation lignin, and then the acid precipitation lignin is subjected to esterification reaction with an esterifying agent to obtain modified lignin, and then the fertilizer core is immersed in a mixed solution containing modified lignin and biochar and dried to obtain a modified lignin / biochar coated slow-release fertilizer. The method for obtaining the biochar is as follows: removing lignin from poplar sawdust to obtain delignified sawdust, then pyrolyzing the sawdust under a protective atmosphere, and then activating the obtained pyrolysis product with alkali to obtain the biochar; The method for obtaining the mixed solution containing modified lignin and biochar is as follows: dissolving a binder in dichloromethane to obtain a solution containing the binder, dissolving modified lignin in 1,4-dioxane to obtain a solution containing modified lignin, mixing the solution containing the binder with the solution containing the modified lignin to obtain a mixed solution, and adding biochar to the mixed solution to obtain a mixed solution containing modified lignin and biochar, wherein the binder is polyvinyl alcohol; In the solution containing the binder, the mass fraction of polyvinyl alcohol is 20% to 40%, in the solution containing the modified lignin, the mass fraction of the modified lignin is 3% to 7%, and the volume ratio of the solution containing the binder to the solution containing the modified lignin is 0.5 to 2:1; In the mixed solution containing modified lignin and biochar, the mass fraction of biochar is 1-5%.

2. The method for preparing a modified lignin / biochar coated slow-release fertilizer according to claim 1, characterized in that: The lignin source is selected from at least one of sodium lignin sulfonate, enzymatic lignin, alkali lignin, and kraft lignin; The acid precipitation pretreatment process is as follows: dissolving the lignin source in water to obtain a solution, adding hydrochloric acid to the solution to adjust the pH to 1-4, settling for 12-24 hours, separating the solid from the liquid, washing and drying to obtain the acid precipitation lignin.

3. The method for preparing a modified lignin / biochar coated slow-release fertilizer according to claim 1, characterized in that: Acid-precipitated lignin and an esterifying agent are used as raw materials and pyridine is used as a catalyst to carry out an esterification reaction to obtain modified lignin. The esterification reaction time is 1 to 3 hours, the reaction temperature is 10 to 50°C, the esterifying agent is selected from one of acetyl chloride, octanoyl chloride, dodecanoyl chloride and hexadecanoyl chloride, the solid-liquid mass volume ratio of the acid-precipitated lignin to the esterifying agent is 0.2 to 1 g: 2 to 7 mL, and the volume ratio of the esterifying agent to pyridine is 0.5 to 2: 0.

8.

4. The method for preparing a modified lignin / biochar coated slow-release fertilizer according to claim 1, characterized in that: The acid-precipitated lignin is dissolved in NN dimethylformamide and ultrasonicated for 2 to 7 minutes, and then pyridine and an esterifying agent are added to carry out an esterification reaction. After the esterification reaction is completed, the obtained reaction liquid is poured into 300 to 700 mL of hydrochloric acid with a mass fraction of 1 to 3% to terminate the reaction, filtered, precipitated, ground and washed with distilled water and ethanol, and then freeze-dried to obtain modified lignin, and the solid-liquid mass volume ratio of the acid-precipitated lignin to NN dimethylformamide is 0.2 to 1 g: 10 to 30 mL.

5. The method for preparing a modified lignin / biochar coated slow-release fertilizer according to claim 1, characterized in that: The process of the lignin removal treatment is as follows: placing poplar sawdust in an alkali solution containing NaOH and Na2SO3 at 90-110°C for 1-10 hours to obtain alkali-boiled poplar sawdust, then soaking the alkali-boiled poplar sawdust in a H2O2 solution for 1-3 hours, adding ammonia water to adjust the pH to 9-11 during soaking, finally washing the sawdust with deionized water until the solution is neutral, and drying to obtain delignified sawdust; The pyrolysis temperature is 650-750°C, the pyrolysis time is 1-3h, and the heating rate is 2-10°C min –1 ; The process of the alkali activation treatment is to mix the pyrolysis product with KOH, the mass ratio of KOH to the pyrolysis product is 3-5:1, and then perform heat treatment under a protective atmosphere, the heat treatment temperature is 650-750°C, the heat treatment time is 1-3h, and the heating rate is 2-10°C min – 1 .

6. The method for preparing a modified lignin / biochar coated slow-release fertilizer according to claim 1, characterized in that: The fertilizer core is urea, and the particle size of the urea is 4-5 mm; the soaking time is 20-40 seconds; in the modified lignin / biochar coated slow-release fertilizer, the thickness of the coating layer is 100-150 μm.

7. A modified lignin / biochar coated slow-release fertilizer prepared by the preparation method according to any one of claims 1 to 6.

8. Use of a modified lignin / biochar coated slow-release fertilizer prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The modified lignin / biochar coated slow-release fertilizer is used for slow-release of nutrients in still water or soil.